Evaluating Educational Credentials of Teachers as Predictor of Effective Teaching: A Pupil Fixed-Effect Modeling Approach - Liu, Ji (Frontiers in Psychology, 2021)
Many factors serve as predictors of effective teaching; particularly, there is an ongoing debate regarding whether the educational credentials of teachers are indicative of their contribution to pupil's educational success. Utilizing pupil fixed-effect modeling and the China Education Panel Survey dataset (n = 5,032), this study evaluates the extent to which teachers who hold at least a Bachelor of Education (BEd) degree perform better than those who do not, in terms of pupil learning gains over the course of a full academic year. Empirical results from the pupil fixed-effect model indicate that mean learning gain is 0.042 SDs (95% CI: 0.008–0.083, p = 0.040) higher among pupils who studied with teachers holding higher educational credentials (at least a BEd degree) than those with lower educational credentials. This effect translates to approximately 1 month of additional learning per year, which is significant considering the potential compounding aggregation effects over the course of the entire educational career of pupils. This study adds new evidence that highlights the importance of the educational credentials of teachers as a predictor of effective teaching and that better-educated teachers can lead to improved pupil learning gains.